2007
DOI: 10.1080/17441690601012536
|View full text |Cite
|
Sign up to set email alerts
|

Use of the non-pneumatic anti-shock garment (NASG) to reduce blood loss and time to recovery from shock for women with obstetric haemorrhage in Egypt

Abstract: Obstetric haemorrhage is one of the leading causes of maternal mortality. In many low-resource settings, delays in transport to referral facilities and in obtaining lifesaving treatment, contribute to maternal deaths. The non-pneumatic anti-shock garment (NASG) is a low-technology pressure device that decreases blood loss, restores vital signs, and has the potential to improve adverse outcomes by helping women survive delays in receiving adequate emergency obstetric care. With brief training, even individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Ensure patient's airway is patent and give oxygen. Several studies including this work have confirmed the effectiveness of the NASG as a first-aid-lifesustaining-device that can sustain the lives of critical ill shock patients until cross matched blood and definitive interventions become available [12][13][14][15][16][17]. The normal saline infusion was limited to 1.5 liter instead of the usual recommendation of 3:1 to avoid fluid overload as the vascular volume is restricted by the NASG application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensure patient's airway is patent and give oxygen. Several studies including this work have confirmed the effectiveness of the NASG as a first-aid-lifesustaining-device that can sustain the lives of critical ill shock patients until cross matched blood and definitive interventions become available [12][13][14][15][16][17]. The normal saline infusion was limited to 1.5 liter instead of the usual recommendation of 3:1 to avoid fluid overload as the vascular volume is restricted by the NASG application.…”
Section: Discussionmentioning
confidence: 99%
“…It is a lower body suit of articulated neoprene and Velcro segments that provides rapidly lower body circumferential counter pressure of 20-40 mmHg that decreases the distal aortic mean baseline blood flow of 1.99 l/min by 0.65, and thus shunts blood flow from the lower limbs and the pelvis to the heart, brain, lungs and kidneys like during the compensatory stage of hypovolemic shock [13,14]. Studies in Egypt and Nigeria on obstetric hemorrhage confirmed that the NASG can reduce pelvic blood loss by 50%, prevent emergency hysterectomy, and shock-related morbidities like irreversible shock, multiple organ failures and maternal deaths [15][16][17]. The aims of this study are to reappraisal the effectiveness of NASG in averting maternal deaths and shock-related morbidities in severe obstetric hemorrhagic shock patients, and to make recommendations.…”
Section: Introductionmentioning
confidence: 94%
“…The use of non-pneumatic anti-shock garments (NASG) is recommended as a temporizing measure until substantive care is available [9,10,11]. The NASG is a low-tech firstaid, re-usable lower-body compression garment which can be used to stabilise women with postpartum haemorrhage [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…For women treated with the NASG, measured blood loss after entry to the study was reduced from 33-78% and the NASG improved maternal *Address correspondence to this author at the Safe Motherhood Program, Department of Obstetrics ,Gynecology and Reproductive Sciences, University of Califormia, San Francisco, 50 Beale Street, Suite 1200, San Francisco , CA 94105, USA; Tel: 4155979343; Fax: 4155979300; E-mail: jemo307@gmail.com survival by 40-67% [7][8][9]. Despite these improved statistics, unexplained maternal morbidity (e.g., anuria, dyspnea) and deaths still occur, even with use of the NASG.…”
Section: Introductionmentioning
confidence: 99%